Casing coupling for extreme temperature setting - Haraldur Orri Björnsson 1984- (2015)
The next leap in utilization of geothermal energy for electricity production might comprise of drilling deep wells down to the roots of geothermal reservoirs. Near these roots fluid at very high temperature and even at supercritical conditions can be accessed. Extraction of such fluid from natural reservoirs can if some obstacles can be conquered revolve geothermal utilization and electricity production. To allow deep geothermal wells to become a viable option a comprehensive research has to be carried out to eliminate all uncertainty regarding the resource. Furthermore the technical challenges which developers face on all stages from drilling and extraction to production have to be solved. One of the most essential parts of a geothermal well is the casing, string of pipes which ensure the structural integrity of a well and seal the well from unwanted fluids from the geothermal reservoir. Successful casing design and installation increases the longevity of a well, while design or installation faults can render a well inoperable or be the cause of high maintenance cost. It has been identified that deep geothermal wells will test a casing string performance further than conventional wells and if deep geothermal wells are to be a feasible option the casing design has to be resilient and reliable. This thesis reviews two threaded casing connection options proposed for extreme temperature settings and aims to answer which if any of examined options are best suited for deep wells of the future using finite element analysis. Assumptions made for the research are to some extent based on the Iceland Deep Drilling Project (IDDP). The results indicate that conventional threaded options can’t be recommended for examined conditions and premium connections with metal to metal sealing surface have no advantages over conventional connections under inspected loads. The results do not highlight any advantages of upgrading the casing to a higher grade material according to API 5CT standard. Næsta stökk í jarðhitanýtingu til ...